2012
DOI: 10.1016/j.homp.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calendula officinalis on human gingival fibroblasts

Abstract: Calendula inhibits HGF-mediated collagen degradation and MMP-2 activity more than the corresponding concentration of quercetin. This may be attributed to additional components in Calendula other than quercetin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(17 citation statements)
references
References 26 publications
1
13
0
2
Order By: Relevance
“…Despite the lack of studies evaluating the effect of the crude extract of CLO on bone tissue, it has been reported that queretin, the main flavonoid found on CLO extract, is the one responsible, in great part, of the pharmacological effects of this plant (Saini et al, 2012). In vitro , quercetin significantly increased osteoblast differentiation (Zhou et al, 2015) and induced mRNA expression of sialoprotein and osteocalcin in osteoblast culture (Satué et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of studies evaluating the effect of the crude extract of CLO on bone tissue, it has been reported that queretin, the main flavonoid found on CLO extract, is the one responsible, in great part, of the pharmacological effects of this plant (Saini et al, 2012). In vitro , quercetin significantly increased osteoblast differentiation (Zhou et al, 2015) and induced mRNA expression of sialoprotein and osteocalcin in osteoblast culture (Satué et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…CLO preserved collagen confirming others studies which already showed that CLO extract reduced collagen breakdown (Millán et al, 2016), and increased collagen concentration (Aro et al, 2015). In gingival fibroblasts, CLO inhibited matrix metalloproteinases (MMP)-2 (Saini et al, 2012). Collagen is the main constituent of periodontal ligament and plays a key role in the architecture of the periodontium (Kaku and Yamauchi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The flowers of C. officinalis are well known for their anti-inflammatory, antipyretic, antitumor, and healing effects (Saini et al 2012;Bortoldo et al 2009) as well as antioxidant activity (Shivasharan et al 2013). These activities are related to the chemical composition of the plant, especially the presence of flavonoids and polyphenols (Butnariu & Coradini 2012;Borella et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides isolated from Calendula officinalis ethanolic fraction have shown antitumor activity (Parente et al 2004). The presences of lutein, lycopene, and xanthophylls, which contribute to anti-oxidant and anti-inflammatory effects, have also been described (Saini et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Junto a estos fibroblastos y otras células de defensa, se producen citocinas pro-inflamatorias (Ara et al 2013, Baek et al 2013) como la Interleucina 1ß (IL 1ß; Bhawal et al 2012, Sawada et al 2013, Factor de Necrosis Tumoral alfa (TNFα; Guimarães et al 2011, Arancibia et al 2013) y citocinas anti-inflamatorias como lainterleucina10 (IL-10); que controla una respuesta inflamatoria exacerbada (Morandini et al 2011, Gómez-Florit et al 2013. De esta forma, la regulación de las funciones de remodelación del tejido conectivo y respuesta inflamatoria de los fibroblastos gingivales con medicamentos antihomotóxicos, podría tener un gran potencial terapéutico en periodoncia (Saini et al 2012). El objetivo de esta investigación, fue establecer el efecto de Mercurius-Heel®S sobre fibroblastos gingivales cultivados in vitro en diferentes tiempos y concentraciones, con el fin de dar una explicación científica al uso del Mercurius-Heel®S en enfermedades orales como la periodontitis.…”
Section: Medición De La Citotoxicidad Y Producción De Citocinas En Fiunclassified